1 Apologia Justyna Męczennika i Platońska Apologia Sokratesa - inspiracja czy polemika? - Heszen, Agnieszka (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The subject of this article is comparison of Justin’s the First Apology and Apology of Socrates by Plato. The first of all, I analysed composition of work of Christian writer, taking as a starting point not rhetorical scheme apology as such, but exactly successive parts of the Socrates’ speech. Justin Martyr took a pattern of this speech for his First Apology, because condition of Christians in the Roman Empire was very similar to situation of Socrates in the Athenian court. The next problem is way, which Justin presented Christian faith. He did this by pagan philosophy, and especially recalling Stoic theory of Logos and some aspects of Plato’s thought. Justin inspired by Platonic ideas and literary forms of his dialogues, propagated and promoted Christian religion. His First Apology is not apology as forensic speech, but it has protreptic character too.
Keywords: Justin Martyr; Plato; apology; Socrates; christianity